Respostas
respondido por:
3
Fazer a equação de acordo com a leitura. Depois utilizar a fórmula.
Anexos:
respondido por:
17
x² - 4x = 5
x² -4x -5 = 0
a = 1
b = -4
c = -5
Δ = b² -4ac
Δ = (-4)² -4.1.(-5)
Δ = 16 + 20
Δ = 36
x = -b ± √Δ /2a
x = -(-4) ± √36 /2.1
x = 4 ± 6 /2
x' = 4+6/2 = 10/2 = 5
x'' = 4 - 6 /2 = -2/2 = -1
Bons Estudos!!
x² -4x -5 = 0
a = 1
b = -4
c = -5
Δ = b² -4ac
Δ = (-4)² -4.1.(-5)
Δ = 16 + 20
Δ = 36
x = -b ± √Δ /2a
x = -(-4) ± √36 /2.1
x = 4 ± 6 /2
x' = 4+6/2 = 10/2 = 5
x'' = 4 - 6 /2 = -2/2 = -1
Bons Estudos!!
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás